Implementation of STEAM-based bioentrepreneurship learning to improve creativity and entrepreneurship in fourth grade elementary school students - Wulandari, Rika; Rahmawati, Ika Dian (Universitas Kanjuruhan Malang, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of coconut-based bioentrepreneurship at SDN Proppo 1 Pamekasan, increasing students' creativity and entrepreneurship through the STEAM approach in the Merdeka Curriculum. This qualitative descriptive study involved the stages of introduction, contextualization, real action, reflection, and follow-up in August–December 2024. Students were taught to make environmentally friendly soap from coconut. The results showed that the implementation of P5 succeeded in increasing students' creativity and entrepreneurial skills. The main supporting factors were local materials and facilitators, while obstacles were limited time and students' initial understanding of entrepreneurship. Reflection showed a positive impact on literacy and STEAM-based learning, as well as practical experience in entrepreneurship, with follow-up for the development of similar activities in the future.